Chess periodicals an annotated international bibliography, 1836-2008 - Di Felice, Gino (McFarland & Co, 2010)
This comprehensive reference work presents detailed bibliographical information about worldwide chess periodicals past to present. It contains over 3,100 entries. Information for each entry includes year and country of publication, frequency, sponsors, publisher, editors, language, subject, and holdings in chess libraries. Includes an alphabetical periodical index and an index of periodicals by country.
Keywords: Chess : Bibliography; Board games : Bibliography